Strengthening Business Collaborations in the Sidoarjo District MSME Community - Nugrahaputra, Muhammad Rafi; Aesthetika, Nur Maghfirah (Indonesian Journal of Cultural and Community Development, 2024)
Background: Effective communication is vital for group dynamics within communities, particularly in business networks. Specific Background: This study focuses on the communication practices of the Micro, Small, and Medium Enterprises (MSMEs) community. Knowledge Gap: While prior research exists, the dynamics of information sharing in such informal settings have not been thoroughly examined. Aims: The research aimed to analyze communication dynamics within an MSME community and identify factors affecting interaction. Results: Findings indicate that informal interactions strengthen relationships and enhance partnership potential, yet information sharing remains limited, with only a few members actively disseminating business-related news. Novelty: This study emphasizes the significance of informal communication in building relationships while highlighting the need for improved information dissemination. Implications: Recommendations include fostering a more flexible communication environment to enhance collaboration and information exchange within MSME communities. Highlights : Informal Interactions: Foster strong relationships among community members. Limited Information Sharing: Only a few members actively disseminate relevant business news. Need for Flexibility: A more inclusive communication environment is essential for collaboration. Keywords: communication, MSMEs, information sharing, community dynamics, partnerships